The circuits and filters handbook. - Chen, Wai-Kai, 1936- (CRC Press, 2009)
Focuses on computer-aided design and design automation. This book addresses such topics as modeling of circuit performances, symbolic analysis methods, numerical analysis methods, design by optimization, statistical design optimization, and physical design automation.